A critical review of digital capability frameworks: a consumer perspective. Issue 4 (10th August 2020) - Malchenko, Yulia; Gogua, Megi; Golovacheva, Ksenia; Smirnova, Maria; Alkanova, Olga
Abstract : Purpose: This study aims to systematize and critically analyse existing indices and frameworks on digital capabilities with the focus on consumers' digital capabilities, identify opportunities for their further development and suggest agenda for future research. Design/methodology/approach: A sample of 18 frameworks and indices of consumers' digital capabilities were compared based on their purposes, stakeholders, scope and application areas. Findings: The study concludes with propositions that generalise current views on conceptualisation, measurement and management of consumers' digital capabilities. Each proposition is further investigated in terms of possible implications for research and practice. Practical implications: The study indicates opportunities for businesses not only to consider consumers as recipients and adopters of digital technologies but also to aim to understand how to proactively involve consumers in value co-creation, help them be better educated and have a comprehensive understanding of potential outcomes of their participation in the digital economy. Social implications: Highlighting individual consumer perspective in existing indices and frameworks will help consider the interests of society and provide win-win opportunities for everyone involved in the digital marketplace through bottom-up engagement in addition to top-down regulation and monitoring. Originality/value: This study contributes to the extant literature threefold: firstly, existing digital capability frameworks and indices are systematized and critically investigated using criteria of stakeholders, purpose and aims; secondly, consumers are identified as principal stakeholder group whose interests are insufficiently presented in existing indices; thirdly, an integrative approach is suggested for a crucial comparison of existing indices, frameworks and their methodology with the focus on consumers' interests.